La natura «antepredicativa» dell’evento - Pasqualin, Chiara (Quaestio, 2024)
Abstract Although the term vorpradikativ is only occasionally employed by Heidegger, it qualifies a central topic of his thinking from mid to late 1920s: the dimension of truth, both in its ontic and ontological meaning. Despite this specific use of the term, I will argue that even the more originary dimension of the truth of Being, that is the focus of Heidegger’s later thinking of Ereignis, can be defined as ≪pre-predicative≫ in various ways. In one sense, Being as Logos can be characterised as pre-predicative because it is neither predicative-assertive logos nor the possible object of theoretical assertions. Second, and more importantly, Being is pre-predicative in the sense that it is pre-linguistic (however, the term vorsprachlich is not part of Heidegger’s terminology). This specific status refers to a triple aspect: a) the meaning of Being is associated by Heidegger with the semantic field of voice (Stimme) and disposition (Stimmung); b) Being unfolds itself in a characteristic ≪lack of language≫ (Sprachlosigkeit); c) Being is the ground of language. Nevertheless, we should be aware that if we refer to Heidegger’s strictly literal use of the term vorpradikativ in the 20s, its meaning does not fully overlap with the semantic area of a conceptualized pre-linguistic dimension.